The geopolitics of transportation in the melting Arctic - Lasserre, Frédéric; Têtu, Pierre-Louis (Edward Elgar Publishing, 2020)
Climate change is significantly impacting the Arctic region, with the melting of permafrost, glaciers and sea ice. The rapidly receding summer sea ice led to the idea that climate change could trigger an expansion of transit shipping in the Arctic. The reality is more nuanced: if Arctic shipping is indeed developing, it is destinational shipping that is expanding, with the opening up of oil, gas and mining sites thanks to high global-resource prices. This is a shift from the situation in the 1990s when the impact of climate change was not helping commercial shipping. Climate change is thus more a helper, not a driver, for the development of transportation in the Arctic. Additionally, climate change also contributes to the thawing of permafrost, which poses a problem for land transportation. Regardless, Russia, the Scandinavian States and Canada continue to develop railway projects in the Arctic largely in support of resource extraction.